KAJIAN LABA AKUNTANSI, TOTAL DAN KOMPONEN ARUS KAS TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Kontesa, Maria (MABIS, 2012)
This study aims to test the cash flow total, accounting income, cash flow from operation activity, cash flow from investing activity and cash flow from financing activity are expected to affect the stock price in annual reporting companies included in the LQ-45 firms in Indonesia Stock Exchange. The sample data used is the company that includes LQ-45 index in the period February 2008 to January 2011 using annual reports from each company for the fiscal year 2008 to 2010. Datas were analyzed by using the classical assumption test and multiple linear regression analysis with SPSS program ver16. The results of this study indicate that the cash flow total and, accounting income had significant effect on stock price in corporate annual reports because if accounting income increase then the investors will investing theirs money in that company, so the companys stock price will be increase too. Results of these studies in line with research conducted by the Triyono dan Jogiyanto Hartono (2000), Vicky Oktavia (2008) and others researchers. From the results of these studies shows that accounting income had significant positif effect on stock price in corporate annual reports, which Results of these studies in line with research conducted by Triyono dan Jogiyanto Hartono (2000) and Vicky Oktavia (2008). As a simultant test the cash flow total accounting income and accounting income had significant positif effect on stock price in corporate annual. Results of these studies had no significant effect on stock price in corporate annual reports between cash flow from investing activity, and cash flow from financing activity on stock price in partial (based on t-test) and simultant test (based on F-test), which Results of these studies not in line with research conducted by Triyono dan Jogiyanto Hartono (2000) and Vicky Oktavia (2008), but in line with research conducted by Dillah Utami Cahyani (1999).Â Â